2014
DOI: 10.1186/1748-717x-9-136
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adapted partial larynx and/or carotid artery sparing modulated radiation therapy of glottic cancer

Abstract: Background: To evaluate outcome in patients with glottic cancer treated with intensity-modulated radiotherapy (IMRT) and to show effectiveness of partial laryngeal-and/or carotid artery sparing in low to intermediate risk tumors. Study design: Retrospective analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In common with other series, late toxicity is patchily documented. There is current interest in the potential for intensity modulated radiotherapy techniques to offer carotid artery sparing [ 36 ]; it was not possible to reliably document the long term risk of cerebrovascular events with conventional radiotherapy in this series.…”
Section: Discussionmentioning
confidence: 99%
“…In common with other series, late toxicity is patchily documented. There is current interest in the potential for intensity modulated radiotherapy techniques to offer carotid artery sparing [ 36 ]; it was not possible to reliably document the long term risk of cerebrovascular events with conventional radiotherapy in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the local infiltration and growth of carcinoma and the advancement of treatment methods, the disease is characterized by a low probability of metastasis. Because EBRT is characterized by a lack of trauma, a good curative effect, and minimal effects on vocal function and quality of life, it is becoming more widely applied for patients with early glottic laryngeal cancer 12 , 13 . Because of its relatively non-invasive nature, good curative effect and minimal influence on vocal function and quality of life, TLM has progressively replaced the use of total laryngectomy/hemi-laryngectomy for early glottic laryngeal cancer patients 4 , 7 .…”
Section: Discussionmentioning
confidence: 99%
“…20 For example, Janssen and colleagues recently reported excellent local control rates in 39 patients with T1-2N0 glottic carcinoma treated with IMRT, including 21 patients that underwent ipsilateral vocal cord irradiation with bilateral carotid sparing resulting in a mean contralateral carotid dose of 20.2 Gy. 21 Since the time period of this study, we have chosen to employ an intermediate approach, using daily image guidance and decreasing our circumferential margin to 0.5cm, with as little as 0.3cm margin allowable near the carotid arteries in order to achieve a more significant reduction in carotid dose. Notably, in this study we found that the benefit of carotid sparing IMRT varied significantly based on a given patient’s anatomy, with mean carotid artery doses ranging from 20.5 Gy to 61.5 Gy.…”
Section: Discussionmentioning
confidence: 99%